RANCANG BANGUN PENGENDALI PERALATAN LISTRIK PADA GEDUNG MENGGUNAKAN JARINGAN NIRKABEL - Sudibyo, Novi Herawadi (Jurnal Informatika, 2014)
Controllers electrical equipment in buildings that have a lot of space require great strength, compounded with a level human error, which can cause bad impact. Viewing from the situation to motivate people to make a controller that can be used to the monitoring and control all the equipment available in each room utilizing existing computer network electrical equipment is installed in a building can be monitored and controlled from long range without having to see one by one to each room is in the building.Keyword : Computer Network, Electronic Equipment, Programming.